STUDI HUKUM PERKAWINAN ISLAM DI INDONESIA PERSPEKTIF GENDER - Musyafa’ah, Nur Lailatul (The Indonesian Journal of Islamic Family Law, 2014)
Abstract: This article discusses Islamic family law from the perspective gender studies. The study of Islamic family law is a compulsory study for all students in the Faculty of Islamic Law and Legal Studies. The study, though, only referred to classical Islamic jurisprudence as reflected in Islamic law school (Maddhab). In addition, it uses the positive law of marriage in Indonesia, namely Law No. 1/1974 on Marriage and Presidential Degree No. 1/1990 on Kompilasi Hukum Islam. With the development of renewal in Islamic family law in contemporary state, Islamic family law should be studied through various approaches, including gender analysis. This is important because many modern muslim scholars formulate the renewal of Islamic family law to achieving gender equality in marriage. They do so by reinterpreting Quranic texts and prophet traditions. If the study of Islamic family law is conducted from, among other things, gender analysis, students will be able to think critically and flexible in discussing contemporary issues of Islamic family law. Abstrak: Tulisan ini mengkaji studi hukum perkawinan Islam dengan pendekatan gender. Hukum perkawinan Islam sebagai mata kuliah wajib yang diajarkan di Fakultas Syariah, masih cenderung merujuk kepada pendapat mazdhab klasik, UU Perkawinan Nomor 1 Tahun 1974, dan Kompilasi Hukum Islam. Dengan perkembangan zaman dan adanya pembaruan pemikiran hukum Islam, perlu dikaji lebih mendalam materi Hukum Perkawinan Islam dengan berbagai pendekatan, salah satunya dengan pendekatan gender. Hal tersebut penting dilakukan, karena telah banyak pemikir modern muslim yang merumuskan adanya pembaruan dalam Hukum Perkawinan Islam demi tercapainya kesetaraan gender dalam perkawinan yang sesuai dengan perkembangan zaman, diantaranya dengan reinterpretasi teks al-Qurâan dan Hadis Hukum Perkawinan. Diharapkan dengan pembelajaran Hukum Perkawinan Islam dengan pendekatan gender, mahasiswa dapat berfikir kritis dan tidak kaku dalam berijtihad tentang masalah KontemporerÂ  Hukum Perkawinan Islam.Kata Kunci:Abstract: This article discusses Islamic family law from the perspective gender studies. The study of Islamic family law is a compulsory study for all students in the Faculty of Islamic Law and Legal Studies. The study, though, only referred to classical Islamic jurisprudence as reflected in Islamic law school (Maddhab). In addition, it uses the positive law of marriage in Indonesia, namely Law No. 1/1974 on Marriage and Presidential Degree No. 1/1990 on Kompilasi Hukum Islam. With the development of renewal in Islamic family law in contemporary state, Islamic family law should be studied through various approaches, including gender analysis. This is important because many modern muslim scholars formulate the renewal of Islamic family law to achieving gender equality in marriage. They do so by reinterpreting Quranic texts and prophet traditions. If the study of Islamic family law is conducted from, among other things, gender analysis, students will be able to think critically and flexible in discussing contemporary issues of Islamic family law. Abstrak: Tulisan ini mengkaji studi hukum perkawinan Islam dengan pendekatan gender. Hukum perkawinan Islam sebagai mata kuliah wajib yang diajarkan di Fakultas Syariah, masih cenderung merujuk kepada pendapat mazdhab klasik, UU Perkawinan Nomor 1 Tahun 1974, dan Kompilasi Hukum Islam. Dengan perkembangan zaman dan adanya pembaruan pemikiran hukum Islam, perlu dikaji lebih mendalam materi Hukum Perkawinan Islam dengan berbagai pendekatan, salah satunya dengan pendekatan gender. Hal tersebut penting dilakukan, karena telah banyak pemikir modern muslim yang merumuskan adanya pembaruan dalam Hukum Perkawinan Islam demi tercapainya kesetaraan gender dalam perkawinan yang sesuai dengan perkembangan zaman, diantaranya dengan reinterpretasi teks al-Qurâan dan Hadis Hukum Perkawinan. Diharapkan dengan pembelajaran Hukum Perkawinan Islam dengan pendekatan gender, mahasiswa dapat berfikir kritis dan tidak kaku dalam berijtihad tentang masalah KontemporerÂ  Hukum Perkawinan Islam.